The Effectiveness of Laboratory Parameters in Predicting the in-Hospital Mortality of Iranian Patients with Coronavirus Disease 2019 (COVID-19) - Kouhsari, E.; Sadeghifard, N.; Karimian, M.; Kalvandi, G.; Sayyadi, H.; Feizi, J.; Ahmadi, I.; Maleki, A.; Kenarkoohi, A.; Kaffashian, M. R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The novel coronavirus 2019-nCoV (now SARS-CoV-2) has spread globally and affected healthcare systems worldwide. Due to lack of long-term immunization and effective specific treatments for the COVID-19 disease, there is a need of identifying the patients who are at the risk of a fatal outcome, according to the available epidemiological data and laboratory parameters.Objective. Thus, we aimed to evaluate the prognostic value of epidemiological data and laboratory parameters for in-hospital case fatality in patients with COVID-19.Materials and Methods. A retrospective cohort of patients with COVID-19 admitted to the Shahid Mostafa Khomeini Hospital of Ilam University of Medical Sciences from February 29 until March 29, 2020 was performed. Epidemiologic data and laboratory results were collected. Univariate and multivariate logistic regression models were performed to evaluate the prognostic value of the laboratory parameters for inhospital death.Results. A total of 256 Iranian COVID-19 patients were included in the evaluation; 38 of them died, resulting in a in-hospital case-fatality rate of 14.8%. The univariate analysis showed that advanced age [OR=1.04, 95% CI: 1.02, 1.06, P=0.001], smoking [OR=4.041, 95% CI: 1.546-10.563, P=0.004], white blood cells [OR=0.941, 95% CI: 0.904-0.980, P =0.003] and hematocrit [OR=1.060, 95% CI: 1.009-1.113, P=0.020] were positively associated with the risk of a fatal outcome. Multivariate logistic regression analysis revealed that COVID-19 patients with an elevated white blood cell count and elevated hemoglobin level had 1% and 9% greater risk of an in-hospital death for each elevated unit [OR=1.07; 95 %CI: 1.024-1.088, P =0.002 and OR=1.379; 95% CI 0.064-1.788, P =0.015, respectively].Conclusions. An increase in white blood cell count and an increase in hemoglobin level might be independent risk factors for in-hospital death in Iranian patients with COVID-19. Further studies are necessary in order to conferm the prognostic value of the variables discussed.